The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41398-018-0356-7
|View full text |Cite
|
Sign up to set email alerts
|

A validation of the diathesis-stress model for depression in Generation Scotland

Abstract: Depression has well-established influences from genetic and environmental risk factors. This has led to the diathesis-stress theory, which assumes a multiplicative gene-by-environment interaction (GxE) effect on risk. Recently, Colodro-Conde et al. empirically tested this theory, using the polygenic risk score for major depressive disorder (PRS, genes) and stressful life events (SLE, environment) effects on depressive symptoms, identifying significant GxE effects with an additive contribution to liability. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 69 publications
2
35
0
Order By: Relevance
“…Our findings are in line with two recent studies, which found no evidence for an interaction between a PRS for major depression and self-reported childhood trauma in adulthood (21) and in childhood/youth (24), respectively. Two studies (37,38), applying similar methods but using self-reported recent SLEs (in adulthood), reported a significant interaction effect in line with the diathesis-stress model. However, the interaction could be induced by the self-reported stress likely being correlated with both genetic risk for depression and the depression outcome, resulting in those who are at higher risk for depression and possibly experiencing depressive symptoms reporting (and subjectively experiencing) more life stress (i.e., recall bias) (37).…”
Section: G3e Interactionmentioning
confidence: 71%
“…Our findings are in line with two recent studies, which found no evidence for an interaction between a PRS for major depression and self-reported childhood trauma in adulthood (21) and in childhood/youth (24), respectively. Two studies (37,38), applying similar methods but using self-reported recent SLEs (in adulthood), reported a significant interaction effect in line with the diathesis-stress model. However, the interaction could be induced by the self-reported stress likely being correlated with both genetic risk for depression and the depression outcome, resulting in those who are at higher risk for depression and possibly experiencing depressive symptoms reporting (and subjectively experiencing) more life stress (i.e., recall bias) (37).…”
Section: G3e Interactionmentioning
confidence: 71%
“…Explanatory power is smaller again for hypothesised multiplicative interactions between PRS and adverse life events (e.g. 0.12%; Arnau-Soler et al, 2019; Colodro-Conde et al, 2018). There is no evidence that any extant G × E score is clinically useful as a risk tool: early studies are showing some promise with the polygenetic risk approach (Fang et al, 2020), but effect sizes lack clinical utility.…”
Section: Aetiology and Pathogenesis Of Mood Disordersmentioning
confidence: 93%
“…Similarly, several environmental exposures have been associated with a schizophrenia spectrum disorder, such as childhood adversities, cannabis use, urbanicity, migration, ethnic minorities, hearing impairment, and perinatal factors (Linszen et al ., 2016; Radua et al ., 2018; Stilo and Murray, 2019). In accordance with the diathesis-stress model, there is evidence supporting gene–environment interaction in the aetiology of schizophrenia (Guloksuz et al ., 2019) and mood disorders (Geoffroy et al ., 2013; Colodro-Conde et al ., 2018; Arnau-Soler et al ., 2019 a , 2019 b ). A recent case-control study found evidence for additive interactions between molecular genetic liability for schizophrenia (i.e.…”
Section: Introductionmentioning
confidence: 99%